Relationship Between Socio-Demographic Characteristics, Reproductive Health Behaviors, and Health Literacy of Women in Serbia - Maricic, Milena; Stojanovic, Goran; Pazun, Vanja; Stepović, Milos; Djordjevic, Ognjen; Macuzic, Ivana Zivanovic; Milicic, Vesna; Vucic, Veroljub; Radevic, Svetlana; Radovanovic, Snezana (Frontiers in Public Health, 2021)
ABSTRACT Introduction: Health literacy of women can significantly affect different aspects of reproductive health. The aim of study is the assessments of relationship of women's health literacy, socio-demographic characteristics and reproductive health behavior of women in Serbia. Methodology: This is a cross-sectional study on a random sample of women aged 18 and over from the territory of three regions in Serbia, stratified according to age groups, region and type of settlement. For testing the health literacy of women a standardized European questionnaire of health literacy was used. Statistical analysis was performed using standard software package SPSS, version 19.0. The minimum level of significance was p <0.05. Results: Results of univariate regression showed that the most important predictors of the health literacy levels were - the type of settlement, education, financial status, employment status and health status. Results of the multivariate regression showed the following significant predictors: commitment to the chosen gynecologist, use of contraception, knowledge of possible damages that be caused by the human papillomavirus, knowledge of the existence of a vaccine against HPV and following of topic related to the health. Conclusion: Limited levels of health literacy were significantly higher among middle-aged women, from rural areas, among those who rated their health as poor or very poor, and who exhibited more negative patterns of reproductive health behavior, indicating the need for implementation of prevention programs and strategies with the aim of increasing the level of health literacy.